2004
DOI: 10.1016/s1054-139x(04)00054-0
|View full text |Cite
|
Sign up to set email alerts
|

Teens speak out about HIV/AIDS: Focus group discussions about risk and decision-making

Abstract: Attempts should be made to make HIV education more relevant for teens so that they use the information they have when making decisions about safer sexual behavior. Different approaches may be needed for boys and girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Reactions to the HIV/AIDS education are similar to what has been found in a related study elsewhere. Hope et al. (2004) found that students had no interest in HIV/AIDS education because they felt that the message delivered was not personally relevant to them.…”
Section: Discussion and Implications For The University’s Hiv/aids Inmentioning
confidence: 99%
“…Reactions to the HIV/AIDS education are similar to what has been found in a related study elsewhere. Hope et al. (2004) found that students had no interest in HIV/AIDS education because they felt that the message delivered was not personally relevant to them.…”
Section: Discussion and Implications For The University’s Hiv/aids Inmentioning
confidence: 99%
“…Although teens know how HIV is transmitted and are aware of the positive and negative outcomes of engaging in risky or unsafe sexual behavior, the information does not seem salient or personally relevant to them and has little bearing on their sexual decision making (Hoppe et al, 2004). Through T 3 , facilitators can identify the kind of information teens find relevant to them because the teens drive the conversation about how and why teens in their community behave the way they do.…”
Section: Rationalementioning
confidence: 99%
“…Through T 3 , facilitators can identify the kind of information teens find relevant to them because the teens drive the conversation about how and why teens in their community behave the way they do. If the information discussed is more real and personal, teens will be more likely to be engaged (Hoppe et al, 2004). …”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation